2020
DOI: 10.1126/science.abd5059
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar nuclei evolved by repeatedly duplicating a conserved cell-type set

Abstract: Cerebellar evolution Cerebellar nuclei, substructures of the cerebellum, transfer information from the cerebellum to other parts of the brain. Using single-cell transcriptomics, Kebschull et al. have now identified a conserved pattern of cerebellar nuclei structure that has been repeated through evolution (see the Perspective by Hatten). Ranging from mice to chickens to humans, cerebellar nuclei are made up of region-specific excitatory neurons and region-invarian… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
147
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 73 publications
7
147
3
Order By: Relevance
“…Cerebellar nuclei derive from the coordinated integration in the nuclear transitory zone of glutamatergic and large glycinergic projection neurons migrating from the RL, and of GABAergic interneuron precursors migrating from the VZ [10]. The development of glutamatergic projection neurons depends on OLIG3 expression [58] and on differential expression of PAX6, T-Box Brain Transcription Factor 1 (TBR1) and LIM Homeobox Transcription Factor 1 Alpha (LMX1A) in the medial cerebellar nuclei, or OLIG2 and LHX9 in the lateral cerebellar nuclei [47].…”
Section: Transcriptome Changes That Accompany Cerebellar Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebellar nuclei derive from the coordinated integration in the nuclear transitory zone of glutamatergic and large glycinergic projection neurons migrating from the RL, and of GABAergic interneuron precursors migrating from the VZ [10]. The development of glutamatergic projection neurons depends on OLIG3 expression [58] and on differential expression of PAX6, T-Box Brain Transcription Factor 1 (TBR1) and LIM Homeobox Transcription Factor 1 Alpha (LMX1A) in the medial cerebellar nuclei, or OLIG2 and LHX9 in the lateral cerebellar nuclei [47].…”
Section: Transcriptome Changes That Accompany Cerebellar Developmentmentioning
confidence: 99%
“…Notably, cerebellar nuclei also receive excitatory inputs from collaterals of both parallel and climbing fibers and send feedback signals to the inferior olive, thus fine tuning the final output of the cerebellar circuitry [ 9 ]. Cerebellar nuclei display a complex cytoarchitectural structure, wherein glutamatergic, GABAergic and glycinergic neurons are stereotypically arranged in functionally distinct subunits [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, beyond the traditional cerebellar functions in supervised motor learning utilizing prediction error, lines of evidence suggest that the cerebellar network machinery is widely involved in the processing, generating, and testing of motor and non-motor predictions ( Sokolov et al, 2017 ; Popa and Ebner, 2018 ; Hull, 2020 ). Furthermore, it has been shown that the cerebellum makes broad projections to multiple brain regions through both direct and indirect pathways ( Kebschull et al, 2020 ). Thus, specific anatomical efferent connections appear to at least be partly responsible for specific cerebellar functions.…”
Section: Introductionmentioning
confidence: 99%
“…All three nuclei of the DCN are embedded in the deep central area of the cerebellum. Even though DCN neurons in general project to a broad area, the overall projecting targets from each nucleus have different characteristics ( Teune et al, 2000 ; Kebschull et al, 2020 ), such as more projections to the brainstem from the FN and more projections to the thalamus or midbrain from the IPN or DN. The anterior and posterior IPNs were also shown to have different projecting patterns ( Teune et al, 2000 ; Lu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation